NEW CYTOPLASMIC COMPONENTS IN ARTERIAL ENDOTHELIA - Weibel, Ewald R. (The Rockefeller University Press, 1964)
A hitherto unknown rod-shaped cytoplasmic component which consists of a bundle of fine tubules, enveloped by a tightly fitted membrane, was regularly found in endothelial cells of small arteries in various organs in rat and man. It is about 0.1 µ thick, measures up to 3 µ in length, and contains several small tubules, ∼150 A thick, embedded in a dense matrix, and disposed parallel to the long axis of the rod. In some of these cells, the cisternae of the endoplasmic reticulum are greatly distended by the accumulation of a dense, finely granular material. The nature and significance of these cytoplasmic components are yet unknown.